Risk management in the corn commodity supply chain as a raw material for sustainable poultry feed: A systematic literature review - Kulsum, Kulsum; Fauzi, Anas Miftah; Sailah, Illah; Suparno, Ono; Lembito, Hoetomo (Universitas Sultan Ageng Tirtayasa, 2024)
Corn is a strategic agricultural commodity due to its benefits and essential role in various sectors. It is not only used for food but also as a raw material for industries, including agro-industry and poultry feed. Approximately 40% to 50% of the raw materials for poultry feed are derived from corn. In the corn supply chain, fulfilling raw material requirements for poultry feed involves several risks that must be addressed, as they can impact the quality, quantity, price, and sustainability of corn. Therefore, it is crucial to identify existing risks, develop appropriate risk mitigation strategies, and implement effective supply chain risk management (SCRM) approaches. This study employs the PRISMA method to conduct a systematic literature review, synthesizing published studies on risks within the corn supply chain as a raw material for poultry feed. Data sources include Scopus, ScienceDirect, Google Scholar, and Semantic Scholar. The initial dataset comprised 1,438 papers, which were filtered to include publications from 2015 to 2023. Using the PRISMA method, the selection process resulted in 124 final reports. The analysis suggests that sustainable SCRM approaches, such as the soft system dynamics methodology (SSDM), have significant potential for application in managing risks along the corn supply chain for poultry feed production.